Remedies for Unfair Terms in Light of the General Principles of EU Law - Elizalde, Francisco de (Wolters Kluwer, 2024)
This paper presents the status quo of the consequences for unfair terms (Art. 6(1) of Directive 93/13, on unfair terms in consumer contracts, UCTD), according to the interpretation of the European Court of Justice (ECJ). In that task, it provides reasons for seemingly contradictory judgments and engages with inconsistent rulings. To navigate these troubled waters, the paper refers to the general principles of EU law, even beyond those that are explicit in the ECJ’s decisions. It is claimed here that those general principles explain the evolution of the remedy for unfair terms and its follow-on consequences. They could also bring light to the clashes between EU law and national private law in the application of the UCTD.
Keywords: 56 Ciencias Jurídicas y Derecho; ODS 16 - Paz, justicia e instituciones sólidas